Chronic conditions and multimorbidity among middle-aged and elderly peri-urban dwellers in Dar es Salaam, Tanzania - Kohler, Stefan; Bärnighausen, Till; Kazonda, Patrick; Leyna, Germana H.; Lohmann, Julia; Killewo, Japhet; Rohr, Julia K.; Stieglitz, Laura-Marie; Paul, Nicolas (International journal of public health, 2024)
Objectives: Chronic conditions and multimorbidity affect care needs and prevention opportunities. Methods: We studied 2,246 men and women aged ≥40 years within the Dar es Salaam Urban Cohort Study from June 2017 to July 2018. Seventeen chronic conditions were assessed based on self-report, body and blood pressure measurement, blood tests, and screening instruments. Results: Hypertension (51.3%), anemia (34.1%), obesity (32.2%), diabetes (31.6%), depressive symptoms (31.5%), low grip strength (21.2%), and ischemic heart disease (11.9%) were widespread. Multimorbidity was common (73.7%). Women had higher odds of obesity, ischemic heart disease, and high cholesterol (adjusted OR: 2.08-4.16) and lower odds of underweight, low grip strength, alcohol problems, and smoking (adjusted OR: 0.04-0.45). Ten years of age were associated with higher odds of low grip strength, cognitive problems, hypertension, kidney disease, chronic cough, diabetes, high cholesterol, ischemic heart disease, and multimorbidity (adjusted OR: 1.21-1.81) and lower odds of HIV infection (adjusted OR: 0.51). Conclusion: We found a higher prevalence of multimorbidity than previously estimated for middle-aged and elderly people in sub-Saharan Africa. The chronic conditions underlying multimorbidity differed by sex.